2003
DOI: 10.1093/jac/dkh028
|View full text |Cite
|
Sign up to set email alerts
|

Clonal dissemination of mupirocin-resistant staphylococci in Greek hospitals

Abstract: In Greece, the rate of mupirocin-resistant S. aureus has remained low and steady since 1999. The high rate of mupirocin-resistant CoNS (33%) in 2002 was due mainly to clonal dissemination of epidemic hospital clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 9 publications
4
20
1
2
Order By: Relevance
“…In the present study, of 29 isolates (30.5%) that presented mupirocin resistance phenotype, of which 41.4% harbored the mupA gene as confirmed as high-level mupirocin resistant MRSA that is lower than the previous rate reported by Abbasi-Montazeri et al (31) from the south-west of Iran (34%) and is higher than India (5%) (32), and Greece (1.6%) (8). In this survey, the resistance of the isolates was confirmed by the amplification of mupA.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In the present study, of 29 isolates (30.5%) that presented mupirocin resistance phenotype, of which 41.4% harbored the mupA gene as confirmed as high-level mupirocin resistant MRSA that is lower than the previous rate reported by Abbasi-Montazeri et al (31) from the south-west of Iran (34%) and is higher than India (5%) (32), and Greece (1.6%) (8). In this survey, the resistance of the isolates was confirmed by the amplification of mupA.…”
Section: Discussionsupporting
confidence: 63%
“…In a study conducted by Shahsavan et al (33), it was shown that 25% of mupirucin resistant MRSA isolates carried the mupA gene. Unrestricted policies that allow the improper and widespread use of mupirocin for long periods in hospitals and health care settings and the origin of the isolates and clinical samples are the most important causes of variation in the incidence rate of resistance to mupirocin in MRSA isolates (8,32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, many other studies from India (25), Greek (26), and Jordan (27) reported low resistance rates of mupirocin among MRSA isolates examined. The high mupirocin resistance rate in burn patients, as demonstrated in the current study, supports the concern that using mupirocin in clinical practice should be revised.…”
Section: Discussionmentioning
confidence: 73%
“…Low prevalence of HLMUPR MRSA strains was previously reported in Korea (1.8%) (35). Unrestricted policies that allow improper and widespread utilization of mupirocin for long periods in hospitals and health care settings and the origin of the isolates and clinical samples are the most important causes of variation in the incidence rate of resistance to mupirocin in MRSA isolates (30)(31)(32). In all, the high resistance rate of mupirocin presented in the current study emphasized that using mupirocin in clinical practice should be modified.…”
Section: Discussionmentioning
confidence: 92%